Investigação de interações telúrio-iodo e iodo-iodo envolvendo a espécie aniônica de diiodetomesitiltelano(II) - Matos, Vinícius da Silva (2025)
This work reports the synthesis, characterization and structural analysis of five new complex salts containing anionic species derived from [MesTeI]. The compounds [Zn(phen)3][MesTeI2(I2)][I3]∙CH3CN (1), [Zn(phen)3][MesTeI2]2∙CH3CN (2), [Zn(bipy)3][MesTeI2]2 (3), [Zn(phen)3][Mes(I)TeI···Te(I)Mes][MesTeI2] (4) and [Zn(phen)3][MesTeI2][MesTeI(I2)(I3)] (5), were characterized by several techniques such as single crystal X-ray diffractometry, infrared vibrational spectroscopy, Raman spectroscopy, 1H, 13C and 125Te magnetic resonance spectroscopy, and elemental analysis. Different stoichiometries of molecular iodine and dimesityl ditellane were explored during the reactions, which gave rise to different anionic species contained in the complex salts (1-5). The intermolecular contacts and interactions of the compounds were explored, mainly the Te∙∙∙I and I∙∙∙I interactions, seeking to understand how the connectivity of the anionic species occurs in each compound. The Hirshfeld surface was used in order to explore and better understand the contacts of interest, as well as the 2D fingerprint graphs. Of note is the novel anionic species [MesTeI(I2)(I3)]- present in compound 5, where a tellurium(II) atom is acting as an acceptor and donor of electron density, participating in multiple bonds at the same time. DFT calculations were used to prove the ambiphilic character of the tellurium(II) center as well as the energy quantification involved in the non-covalent bonds.